Il linguaggio rituale gregoriano - Sitta, Sebastiano (Rivista Italiana di Filosofia del Linguaggio, 2014)
Although plainchant has always been classified among musical forms, it has some characteristics that make it a complex language. It is known that, during Antiquity, Latin had a sort of melodic pronunciation that depended on prosodic elements such as the position of tonic accents and the syllabic quantity. The fact can be recognized both in the Classical and in the Late Antiquity. So it was a common idea that music and rhetoric were tightly connected. With the advent of Christianity the role of words gained more and more importance, since they were tied to the Word, identified with Christ, that represents an ideal model for the creatural world. Plainchant increases the musical characteristics of the ritual words and expands their semantic role in the phrase. It can be observed that certain forms of musical emphasis correspond to the words that have the highest semantic weight in that context. Thus plainchant is not only a musical form but also a semantic-weighted markup language, that is a complex ritual language in which phonology, semantic and rituality are expressed in an artistic form.